2019
DOI: 10.1177/1078155219882081
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of adverse drug reactions and drug–drug interactions with pediatric oncology patients in a south Indian tertiary care hospital

Abstract: Objective The present study was conducted to evaluate the pattern of occurrence of adverse drug reactions and drug–drug interaction in a pediatric oncology unit of a tertiary care hospital. Methods A prospective, observational study was conducted in the Department of Pediatric Oncology, Sri Ramachandra Medical College and Hospital, India. Patients were monitored actively for the occurrences of any adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…Hematological toxicity is one of the uncommon adverse reactions. Mild and recurrent myelosuppression in terms of leukopenia, anemia, and neutropenia ( Johnson et al, 1963 ; Niu et al, 2018 ; Joseph et al, 2020 ) in addition to severe myelosuppression and thrombocytosis may occur ( Carbone et al, 1963 ; Kaufman et al, 1976 ). Different degrees of alopecia may also develop ( Gidding et al, 1999 ), and the reported incidence associated with VCR ranges from 8 to 23.1% ( Niu et al, 2018 ; Joseph et al, 2020 ).…”
Section: Vcr and Vipnmentioning
confidence: 99%
See 2 more Smart Citations
“…Hematological toxicity is one of the uncommon adverse reactions. Mild and recurrent myelosuppression in terms of leukopenia, anemia, and neutropenia ( Johnson et al, 1963 ; Niu et al, 2018 ; Joseph et al, 2020 ) in addition to severe myelosuppression and thrombocytosis may occur ( Carbone et al, 1963 ; Kaufman et al, 1976 ). Different degrees of alopecia may also develop ( Gidding et al, 1999 ), and the reported incidence associated with VCR ranges from 8 to 23.1% ( Niu et al, 2018 ; Joseph et al, 2020 ).…”
Section: Vcr and Vipnmentioning
confidence: 99%
“…Mild and recurrent myelosuppression in terms of leukopenia, anemia, and neutropenia ( Johnson et al, 1963 ; Niu et al, 2018 ; Joseph et al, 2020 ) in addition to severe myelosuppression and thrombocytosis may occur ( Carbone et al, 1963 ; Kaufman et al, 1976 ). Different degrees of alopecia may also develop ( Gidding et al, 1999 ), and the reported incidence associated with VCR ranges from 8 to 23.1% ( Niu et al, 2018 ; Joseph et al, 2020 ). Other rare side effects associated with VCR include fever, gastrointestinal ulcers and perforation, myocardial infarction, rashes ( Niu et al, 2018 ; Joseph et al, 2020 ).…”
Section: Vcr and Vipnmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the research strategies defined previously, 7,712 studies were retrieved from PubMed database. Forty articles were considered relevant for eligibility and finally, considering inclusion and exclusion criteria, 14 studies were included in the systematic review (Collins et al, 1974;Mitchell et al, 1988;Queuille et al, 2001;Le et al, 2006;Gallagher et al, 2012;Posthumus et al, 2012;Barrett et al, 2013;Call et al, 2014;Langerová et al, 2014;Makiwane et al, 2019;Dittrich et al, 2020;Joseph et al, 2020;Morales-Ríos et al, 2020;Workalemahu et al, 2020). Due to the characteristics of studies found, a meta-analysis was considered not feasible to be carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 studies included, six were carried out in pediatric oncology and hematology patients, and eight were carried out in general pediatrics and included a clear pediatric oncohematology subgroup. Four studies (Collins et al, 1974;Mitchell et al, 1988;Queuille et al, 2001;Le et al, 2006) were published before 2010, and 10 studies (Gallagher et al, 2012;Posthumus et al, 2012;Barrett et al, 2013;Call et al, 2014;Langerová et al, 2014;Makiwane et al, 2019;Dittrich et al, 2020;Joseph et al, 2020;Morales-Ríos et al, 2020;Workalemahu et al, 2020) were published later.…”
Section: Resultsmentioning
confidence: 99%